2016
DOI: 10.1111/deci.12219
|View full text |Cite
|
Sign up to set email alerts
|

Linking Electronic Medical Records Use to Physicians’ Performance: A Contextual Analysis

Abstract: Electronic Medical Records (EMR) studies have broadly tested EMR use and outcomes, producing mixed and inconclusive results. This study carefully considers the healthcare delivery context and examines relevant mediating variables. We consider key characteristics of: (i) interdependence in healthcare delivery processes, (ii) physician autonomy, and (iii) the trend of hospital employment of physicians, and draw on theoretical perspectives in coordination, shared values, and agency to explain how the use of EMR c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 107 publications
(218 reference statements)
2
32
0
Order By: Relevance
“…= .09, t = 1.43, p > .10). These results are consistent with recent healthcare IT and OM studies that have employed similar methods and obtained similar results (Dobrzykowski & Tarafdar, ). Summarizing the results, informal relational governance and formal incentive system governance mechanisms appear to work in tandem to moderate the relationships among strategy, structures/processes, and performance.…”
Section: Resultssupporting
confidence: 92%
“…= .09, t = 1.43, p > .10). These results are consistent with recent healthcare IT and OM studies that have employed similar methods and obtained similar results (Dobrzykowski & Tarafdar, ). Summarizing the results, informal relational governance and formal incentive system governance mechanisms appear to work in tandem to moderate the relationships among strategy, structures/processes, and performance.…”
Section: Resultssupporting
confidence: 92%
“…While physician employment may seem to be a silver bullet in improving downstream (hospital) performance, healthcare service research has revealed that it has no effect on employed physicians’ HIT use (Bishop, Shortell, Ramsay, Copeland & Casalino, ) nor improvements in key outcomes such as satisfaction scores, lengths of stay, mortality rates, or 30‐day readmissions rates for most conditions (Budryk, ). Early HIT studies from operations and supply chain researchers have revealed important cognitive and relational mediating factors as key to improving patient satisfaction and physician performance when employing physicians (Dobrzykowski & Tarafdar, , ) as well as associations between physician employment and reduced supply expense (Abdulsalam, Gopalakrishnan, Maltz & Schneller, ) and improved supply chain performance (Nyaga, Young & Zepeda, ; Young et al., ). These early studies provide a useful starting point for additional research into the nuanced mediating and moderating relationships, as well as the more directional strategy—outcomes relationships, that involve physician employment as a hospital—physician coordination mechanism.…”
Section: Regulatory Effects and Nuances Of The Healthcare Supply Chaimentioning
confidence: 99%
“…In other words, lack of training and education of supply chain professionals and executives is a common barrier [17,61], as is proneness to issues like sharing information, which pivots on organizational culture [17]. Variables like shared values have proven to play a mediating role between other variables, such as the use of electronic medical records and physicians´performance [120], while willingness to support the implementation of practices depends on individual interests and the degree to which they make true sense for employees, patients, and the community [50].…”
Section: Staff and Community Behaviormentioning
confidence: 99%